Overcoming Shrimp Farming Problems: Developing Effective Strategies for Boosting Business Competitiveness and Productivity - a Case Study of Company X Shrimp Farming Site, Lamongan - Primartono, Masegi; Agus Prasetio, Eko (Riviera Publishing, 2024)
This study aims to identify critical issues and formulate effective strategies to enhance competitiveness and productivity while developing a sustainable shrimp aquaculture framework. The methodology employed includes both qualitative and quantitative approaches, involving a comprehensive literature review, analysis of current industry practices, and a case study of Company X's operations. Stakeholder interviews, field observations, and data analysis form the basis of this empirical research. The study also explores technological innovations and best industry practices, evaluated against existing practices at Company X. The findings of this research indicate that although the company has adopted several best practices, there is still room for improvement in disease management and operational efficiency. Consequently, this study proposes a series of specific strategies, including technology integration, process optimization, and market expansion, to enhance productivity and business competitiveness. The implications of these findings are that the implementation of these strategies can assist Company X and similar entities in improving their operational performance, supporting the development of sustainable shrimp aquaculture, and addressing competitiveness challenges in the industry.